Using ESA (Engage, Study, Activate) Method for Improving Students’ Speaking Ability at Junior High School - Mega Fithria; Ratmanida Ratmanida (Journal of English Language Teaching, 2019)
AbstractThis paper aims to explain how to improve students’ ability in speaking at Junior High School by using ESA (Engage, Study, Activate) method. Speaking is one of the language skills that should be mastered by students in learning English, especially for Junior High School students. In learning speaking, the students should be able to have a good ability in speaking. They have to participate actively and create a life communication in speaking class. However, students have some problems in learning speaking. The students are not confident to share their idea and afraid of making mistakes in learning speaking. Furthermore, they keep using their own language (mother tongue). The students have low motivation because the teacher still uses conventional method in teaching speaking. Considering the problems, an appropriate method is needed to help students improve their speaking ability as well as to overcome their problems and weakness.  The writer introduces ESA (Engage, Study, Activate) method. In this method, firstly the teacher gets the class interested and engaged, then they study something, and then they try to activate it by putting it into production.Keywords: Teaching Speaking, ESA Method, Junior High School